Asahel Curtis and his camera at a roadhouse, on the White Pass or Skagway Trail. - Curtis, Asahel, 1874-1941 (1897)
Unidentified man at left. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number